Economic and financial evaluation of a biodigester implementation in a dairy farm in the dairy basin of Santa Fe. - ROSTAGNO, M. N. (Universidad Nacional del Litoral, 2020)
The objective of this paper is to evaluate the technical feasibility and economic convenience of a biodigester installation, to obtain biogás and biofertilizer as an alternative for the treatment of effl uents in a dairy farm in the central dairy basin of Santa Fe, considered as a case study. The pollution generated currently from the effl uents is assessed, a situation without a project, and comparedwith the projected benefi t from the proposed investments derived from the savings in the purchase of fertilizers and the generation of biogás. The project is technically, economically and fi nancially feasible for the case analysed. The use of biodigesters is an interesting alternative to give value to organic waste.